Interdependence of Special Education Teachers’ Attitudes and Pedagogical Interaction: Structural and Dynamic Aspects - Ruškus, Jonas (Acta Paedagogica Vilnensia, 2003)
The article presents the results of the social empirical research which was carried out in Lithuanian special schools for mentally disabled. The research problem is: 1) how can special education teachers’ attitudes be characterized in the context of Lithuanian special education paradigms change?; 2) what are the dynamic and structural features that may characterize the relationship between teacher’s attitudes and pedagogical interaction in the classroom? Research hypothesis was: 1) the structure of special education teacher’s attitude is characterized by cultural peculiarity and cross-cultural equivalence; 2) special education teacher’s attitudes are related to pedagogical interaction in the classroom. The scale of attitudes has been constructed according to L. Thurnstone methodology of attitude research. 423 special education from special schools for children with mental disability have been interviewed. On the basis of factor analysis the structure of a special educator’s professional attitude has been determined. The attitude consists of the components of professional motivation (Cronbach a= 0.82), educational authoritarianism (Cronbach a = 0.64), and the representation of handicap (Cronbach a== 0.61). The two-cluster model (K-Mean method) revealed that special education teachers could be classified according to the valence of their attitudes. The first cluster consisted of 300 teachers who received if not high but still favourable test scores. The second cluster included 123 teachers who received low, unfavourable test scores of the measured dimensions. Three special education teachers have been selected for the further research in the interaction between special education teacher’s attitudes, pedagogical interaction with mentally disabled children. The subjects have been selected on the basis of research into the attitudes of special education teachers. Manifestation of special education teacher’s altitudes in pedagogical interaction was studied using an observation method. A standardized observation matrix based on Flanders’ (1970), De Landsheere’s (l ’)76) and Bales’ ( 1970) methodological guidelines and interaction categories were constructed to observe how teachers with different valences of altitudes construe their pedagogical interaction in a different way. Research results showed that the major factor distinguishing teachers with favourable attitudes from those with unfavourable ones in terms of pedagogical interaction is an individualized approach towards students. Special education teacher with favourable attitudes bases higher pedagogical interaction in the special education class on individualized activity combining it with a group approach. Whereas the teacher with unfavourable attitudes applies little individual approach and prefers working with the whole class as a unit. Depersonalized, mass teaching method and negative evaluation of the student reflect an authoritarian character of pedagogical interaction which is characteristic to the teacher with unfavourable attitudes. Students’ action is adequate to that of the teacher’s. During lessons of the teacher with favourable attitudes, students act adequately in terms of verbal behaviour and activeness. Their activity is characterized by stability and regularity. Meanwhile students’ verbal behaviour is not adequate and they are less active in lessons of teacher with unfavourable attitudes. The students’ adequate behaviour is irregular.